Rose without prickle: genomic insights linked to moisture adaptation. Issue 12 (22nd May 2021) - Zhong, Mi-Cai; Jiang, Xiao-Dong; Yang, Guo-Qian; Cui, Wei-Hua; Suo, Zhi-Quan; Wang, Wei-Jia; Sun, Yi-Bo; Wang, Dan; Cheng, Xin-Chao; Li, Xu-Ming; Dong, Xue; Tang, Kai-Xue; et al.
Abstract: Prickles act against herbivores, pathogens or mechanical injury, while also preventing water loss. However, whether prickles have new function and the molecular genetics of prickle patterning remain poorly explored. Here, we generated a high-quality reference genome assembly for 'Basye's Thornless' (BT), a prickle-free cultivar of Rosa wichuraiana, to identify genetic elements related to stem prickle development. The BT genome harbors a high level of sequence diversity in itself and with cultivar 'Old Blush' ( R. chinensis ), a founder genotype in rose domestication. Inheritance of stem prickle density was determined and two QTL were identified. Differentially expressed genes in QTL were involved in water-related functions, suggesting that prickle density may hitchhike with adaptations to moist environments. While the prickle-related gene-regulatory-network (GRN) was highly conserved, the expression variation of key candidate genes was associated with prickle density. Our study provides fundamental resources and insights for genome evolution in the Rosaceae. Ongoing efforts on identification of the molecular bases for key rose traits may lead to improvements for horticultural markets.